Effect Of Different Solvents On Plant Extracts For Their Antifungal Activity Against Alternaria Solani, The Causual Agent Of Early Blight Of Tomato Under In Vitro (Journal of Plant Disease Sciences, 2020)
In present study the effective solvent for plant extracts to increase their antifungal activity were analyzed against A.solani. the plant samples of Neem, Aloe vera, Tulsi, veld grape and Turmeric extract was extracted by using three solvents of sterile distilled water, absolutre ethanol and absolute methanol. The prepared extracts were screened against A.solani by using “poision food technique”, with concentration of 15%, 20% and 25% for water extract and 1.5%, 3% and 5% respectively. The methanol extracts showed their superiority in all cases, followed by ethanol and water extract, but in Tulsi water extract 25% showed maximum growth inhibition which is higher than the alcoholic extracts. Among all plant extracts methanolic extract of Turmeric rhizome extract showed maximum growth inhibiotion of 73.55% followed by Veld grape extract inhibited 69.31% of mycelia growth. In ethanol and water extract also Turmeric rhizome extract showed maximum growth inhibiton of 68.25% and 67.73% at their higher concentration of 5% and 25% respectively. All plant extracts have their fungicidal potential to be developed as potent fungicides in organic farming and Integrated Disease Management.
Keywords: Early blight; Tomato; Plant extract; Antifungal activity